Evaluation of some soil applied insecticides against cutworms on cabbage and tomato - Sharma, S D Sharma (Indian Journal of Plant Protection, 2020)
Field experiments were conducted in cabbage and tomato crops to evaluate efficacy of some chemicals applied in the soil at the time of transplanting for the management of cutworms in Kullu valley of Himachal Pradesh. The findings of the two years experiments revealed that all the chemical treatments used against the cutworms were significantly superior to control in protecting cabbage seedlings from cutworms at 4, 7 and 10 days after its transplanting. A treatment consisting of mixture of methyl parathion (Folidol 2% dust) @ 15 kg/ha and carbofuran (Furadan 3G) @ 15 kg / ha (T4) was found to be highly effective in both cabbage and tomato crops minimizing the infestation of cutworms with 92.3, 94.5 and 100 per cent reduction over the control in cabbage and with 95.0, 94.1 and 100 per cent reduction over control in tomato crop at 4, 7 and 10 days of transplanting, respectively. Based on the yield data of two years, treatment (T4) recorded the highest mean yield (360.6q/ha) with 31.7% increase in yield over control in case of cabbage crop and in tomato, it recorded the highest yield of 475.4 q/ha with 25.5% increase in yield over control.